Implementasi Kearifan Lokal Dalam Pembelajaran Seni Tari Di SMPN 1 Sukadana - Oktariani, Dwi; Ghozali, Imam; Y. Silaban, Christianly (CV. Multi Kreasi Media, 2024)
This research aims to describe the activities of implementing local wisdom in Arts and Culture learning at SMPN 1 Sukadana and to describe how local wisdom is applied by Arts and Culture teachers at SMPN 1 Sukadana. The method used is descriptive qualitative, which describes research data in words. The data source consists of informants, namely arts and culture teachers at SMPN 1 Sukadana who were interviewed, observed and carried out documentation techniques to determine the depth of data needs. Validity testing uses triangulation with data analysis in the form of data reduction, data presentation and drawing conclusions. The results of the research show that the implementation of local wisdom values ​​in dance learning at SMPN 1 Sukadana is highlighting the Jepin Senggayong dance into the learning process, students learn dance with teachers and informants they get outside the school environment. The teacher develops his own learning that is linked to the traditions and cultural results of the Malay community in North Kayong Regency through the Project Assignment learning method where students look for information related to the Jepin Senggayong dance from their area to be practiced in front of the class in groups. The teacher also provides PPTs and videos about the form. -a form of local wisdom in North Kayong. The appreciation shown by students is that they can interpret and appreciate the Jepin Senggayong dance which originates from their area, namely North Kayong Regency and can minimize students' boredom with a monotonous learning system.